In Vivo Whole‐Nerve Electrophysiology Setup, Action Potential Recording, and Data Analyses in a Rodent Model. Issue 11 (8th November 2021) - Zhao, Diane; Behzadian, Negin; Yeomans, David; Anderson, T. Anthony
Abstract: In vivo rodent, whole peripheral nerve models are useful for studying the electrical conduction of sensory and motor fibers under normal physiological conditions as well as for assessing neurological outcomes after the application of physical alterations or pharmacological agents to the nervous system. Significant literature has focused on single‐neuron and central nervous system electrophysiology protocol development. However, creation and development of in vivo whole‐nerve electrophysiological recording protocols are sparse in the scientific literature. Here, detailed protocols for designing and building an in vivo whole‐nerve electrophysiology system are described, including straightforward techniques to create working stimulation and recording electrodes that may be adapted to numerous study designs. Further, we include details for rodent anesthesia, surgical dissection (for the sciatic nerve), compound action potential signal optimization, data acquisition, data analyses, and troubleshooting tips. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : In vivo electrophysiology system wiring, hardware, and software setups Support Protocol 1 : Design and 3D printing of electrophysiology base electrodes Support Protocol 2 : Building needle electrodes Basic Protocol 2 : Rodent anesthesia and surgery for nerve exposure Basic Protocol 3 : Compound action potential recording and troubleshooting using WinWCP Basic Protocol 4 : Compound action potential data analysis using WinWCP